Psycho-educational therapy among Nigerian adult patients with epilepsy: a controlled outcome study (2001)
Psychological interventions in relation to epilepsy are worthy of empirical investigation since there is broad agreement that the psycho-social problems of epilepsy are often more disabling than the seizure attacks. The present study using a controlled outcome design evaluated the efficacy of a 2-day psycho-educational program among patients with epilepsy in Nigeria. The psycho-educational program is the consequence of a two-stage study design, which set out to identify and evaluate psycho-social factors that determine interictal psychopathology in people with epilepsy. Thirty out-patients matched according to seizure type and frequency of seizures were randomly assigned to treatment (n515) or waiting-list control (n515) groups. The major outcome measures used were knowledge about illness schedule, the Becks depression inventory and the Crown–Crisp experiential index. Significant differences between the two groups were found on the three major scales used. The treatment group by within-group analyses, showed a substantial significant decrease in level of depression, a significant increase in the knowledge about epilepsy as well as a significant decrease in all measures of neurotic disorders except for hysterical sub-scale.